The Intracellular Cryoprotectant Effects in Preserving Goramy Spermatozoa after Two Days Sub-Zero Freezing - Abinawanto, Abinawanto; Fitrianingrum, Nisa; Lestari, Retno; Sudaryono, Agung; Rostika, Rita; Fujaya, Yushinta (Indonesian Aquaculture Society (MAI), 2015)
The spermatozoa quality of goramy two days after sub-zero freezing was examined. The quality of spermatozoa examined included motility, viability, and abnormality. We aimed to determine the optimum concentration of glycerol protecting spermatozoa during preservation. We used 0%, 1%, 3%, 5%, 7%, and 9% of glycerol, respectively. Sperms were diluted by the combination of glycerol and fish ringer (1 part of sperm + 3 part of solvent). The dilute sperms were then equiliberated at 4°C for 45 min, and were freezed at -34°C for two days. Thawing was then carried out at 30°C for 2 min. Based on Dunnet test, 5% of glycerol was the optimum concentration maintaining spermatozoa motility (75.95±4.76)%.Keywords: glycerol; Osphronemus goramy; spermatozoa motility, viability, and abnormality; sub-zero freezing